Dietary Supplementation of Flaxseed (Linum usitatissimum L.) Alters Ovarian Functions of Xylene-Exposed Mice - Radoslava Vlčková; Drahomíra Sopková; Zuzana Andrejčáková; Martina Lecová; Dušan Fabian; Zuzana Šefčíková; Alireza Seidavi; Alexander V. Sirotkin (Life, 2022)
The aim of the performed study was to examine the ability of xylene, flaxseed, and their combinations to affect morphological and endocrine indexes of murine ovaries. The 72 indexes of secondary and tertiary follicular cells, oocytes, corpora lutea, and ovarian stroma have been quantified: diameter, markers of proliferation PCNA and apoptosis caspase 3, receptors to FSH, oxytocin, estrogen (alpha and beta), and progesterone. In addition, concentrations of the ovarian hormones progesterone, estradiol, and IGF-I in the blood, as well as their production by isolated ovaries cultured with and without gonadotropins (FSH + LH mixture), were determined using histological, immunohistochemical, and immunoassay analyses. The character of xylene and flaxseed effects on ovarian functions in mice depended on the stage of ovarian folliculogenesis. It was shown that flaxseed could mitigate and prevent the major (63%) effects of xylene on the ovary. In addition, the ability of gonadotropins to affect ovarian hormone release and prevent its response to xylene has been shown. The effects of these additives could be mediated by changes in the release and reception of hormones. These observations suggest that flaxseed and possibly gonadotropins could be natural protectors of a female reproductive system against the adverse effects of xylene.